Professor Rodney J. Landreneau: an uneasy development of VATS over the past 25 years - He, Chao-Xiu (Melanie); Lun, Cliff (Video-Assisted Thoracic Surgery, 2017)
The 4th International Uniportal VATS Course-Live Surgery and Wetlab came to an end in Berlin on 4th March 2017. During the course, we were glad having an interview with Professor Rodney J. Landreneau, Director of Esophageal and Lung Institute of University in Pittsburgh.